The water and nutrient potential of brewery effluent for hydroponic tomato production - Power, Sean Duncan (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2014)
Brewery effluent that had undergone treatment in an anaerobic digester (AD) was used as an alternative water and nutrient source for hydroponic crop production. Brewery effluent was demonstrated to contain sufficient nutrients to support the growth, flowering and fruiting of Lycopersicum escolentum "Moneymaker" tomato crops. The adjustment of the effluent pH with phosphoric acid to between pH 6.0 and 6.5 increased the development of the crops by around 100% compared to crops grown in unaltered effluent. The pH adjusted effluent-grown plants grew to a mean height of 831.4 ± 21.1 mm and a dry biomass weight of 42.34 ± 2.76 g compared to the unaltered pH effluent plants which grew to a height of 410.6 ± 20.5 mm and a weight of 7.65 ± 0.68 g after 49 days. Effluent treatment in high-rate algal ponds (HRAP) was determined to have no positive effect on the nutritional potential of the effluent for Moneymaker production. The effluent-grown plants did not perform as well as plants grown in inorganic-fertilizer and municipal water. Plants grown in effluent grew taller but did not produce significantly more fruit when phosphoric acid (height: 1573.3 ± 50.4 mm, 19.4 ± 1.4 fruit per plant) was compared to nitric acid (height: 1254.1 ± 25.4 mm, 15.6 ± 1.5 fruit per plant) as the pH adjustment over 72 days. Direct and secondary plant stresses from effluent alkalinity, ammonium nutrition, nitrogen limitation, sodium concentrations and heat stress among other factors were probably confounding variables in these trials and require further investigation. Considering the raw effluent composition and manipulating the AD operation is a potential opportunity to improve overall AD performance, reduce chemical inputs in the effluent treatment process, reduce the final effluent alkalinity, and increase available nitrogen content in the final effluent. The anaerobic digester discharging >1000 m³ of nutrient enriched effluent every day is a resource with considerable potential. The benefits of developing this resource can contribute to cost-reduction at the brewery, more efficient water, nutrient and energy management at the brewery, and offer opportunities for job creation and potentially benefit local food security.
Keywords: Hydroponics; Tomatoes -- Breeding; Brewery waste; Water -- Purification; Algae culture; Algae -- Biotechnology; Nitric acid; Phosphoric acid